PENGARUH ARAH GROOVING BETON TERHADAP TAHANAN GESER PERKERASAN KOMPOSIT BETON SEMEN-ASPAL - R. Anwar Yamin; Abdul Halim; Eddie Djunaedi (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
Overlaid asphalt onto concrete pavement is another alternative than regrooving; it creates a composite layer of concrete-asphalt. Monolithic concrete-asphalts depend on bonding at its interface and affected by direction, space and depth of grooving, quantity and may type of tack coat used. This research aimed to know the effect of grooving direction to shear resistance the interface of on concrete-asphalt composite layer. Three types of grooving: transversal, angle of 45o and longitudinal, used. Emulsied asphalt of CRS-1 and cut back asphalt of RC-70 by quantity of 0, 2 l/m2 and 0, 6 l/m2 applied as a tack coat. As the results, it is known that shear resistance the interface of on concrete-asphalt composite layer affected not only on grooving direction but also quantity of tack coat and normal force applied. For concrete-asphalt composite layer, the highest shear resistance given by transversal grooving direction and 45o angle of grooving direction is better than longitudinal grooving. For all grooving direction, CRS-1 emulsified asphalt has a higher shear resistance than RC-70 cut back asphalt and changing of adhesiveness of RC-70 caused of normal force is more susceptible than CRS-1.